Is routine distal clavicle resection necessary in rotator cuff repair surgery? A systematic review and meta-analysis. (May 2019) - Livingstone, Ann; Asaid, Rafik; Moaveni, Afshin Kamali
Background: The objective of the present study was to perform a systematic review and meta-analysis of randomized controlled trials looking at the effect of distal clavicle resection in patients undergoing rotator cuff repair (RCR). Methods: A systematic literature search was undertaken to identify randomized controlled trials looking at RCR +/– distal clavicle resection. Primary clinical outcome measures included in the meta-analysis were American Shoulder Elbow Society (ASES) score, pain on visual analogue scale and range of motion in forward elevation. Results: The systematic review identified three studies with a total of 203 participants. Those who underwent distal clavicle resection in conjunction with RCR had worse pain and acromioclavicular joint tenderness at 3-month follow-up. This difference, however, was not observed at the 24-month follow-up. The mean difference (95% confidence interval) for the ASES score was 0.45 (–3.67 to 4.58) and pain on visual analogue scale was – 0.27 (–0.70 to 0.16). Conclusions: Routine distal clavicle resection in the setting of rotator cuff repair does not result in improved outcomes for patients with no difference being observed at 24 months post surgery. The results of our systematic review and meta-analysis do not support routine distal clavicle resection when performing RCR.